2016
DOI: 10.1021/acs.biochem.6b00006
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic and Hydrophobic Interactions Mediate Single-Stranded DNA Recognition and Acta2 Repression by Purine-Rich Element-Binding Protein B

Abstract: Myofibroblast differentiation is characterized by an increased level of expression of cytoskeletal smooth muscle α-actin. In human and murine fibroblasts, the gene encoding smooth muscle α-actin (Acta2) is tightly regulated by a network of transcription factors that either activate or repress the 5' promoter-enhancer in response to environmental cues signaling tissue repair and remodeling. Purine-rich element-binding protein B (Purβ) suppresses the expression of Acta2 by cooperatively interacting with the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…23,40 Hence, a P223L substitution in the linker region may alter the spatial orientation of intermolecular and intramolecular domains in a manner which enhances MSY1-binding affinity. In contrast to results of comparative DNA-binding assays, quantitative analysis of the binding of Purβ to corepressor partner MSY1 indicated that the P223L and R297Q substitutions altered protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23,40 Hence, a P223L substitution in the linker region may alter the spatial orientation of intermolecular and intramolecular domains in a manner which enhances MSY1-binding affinity. In contrast to results of comparative DNA-binding assays, quantitative analysis of the binding of Purβ to corepressor partner MSY1 indicated that the P223L and R297Q substitutions altered protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
“…40 Some modifications to the process were necessary to optimize the production and purity of the Purβ variants as outlined in the Supporting Information. 40 Some modifications to the process were necessary to optimize the production and purity of the Purβ variants as outlined in the Supporting Information.…”
Section: Recombinant Protein Purificationmentioning
confidence: 99%
See 3 more Smart Citations